THE IMPACT OF BRAND TRUST AND PERCEIVED QUALITY ON BRAND LOYALTY IN MEDIATION CUSTOMER SATISFACTION: A CASE STUDY OF KOPI KENANGAN CONSUMERS IN MEDAN CITY - Friti Sinta; Prihatin Lumbanraja; Beby Karina F. Sembiring (RADJA PUBLIKA, 2023)
In this study, we examined the influence of brand trust and perceived quality on brand loyalty through customer satisfaction at Kopi Kenangan Sun Plaza in Medan City. The increasing consumption of coffee in Indonesia has led to the development of coffee shop businesses in various cities across the country, including Medan. While this growth presents an opportunity for entrepreneurs to build and promote their brands to attract customers, it also creates intense competition among businesses, especially in major cities like Medan. The aim of this research is to find solutions to address the challenges faced by Kopi Kenangan, including low brand trust, perceived product quality, customer satisfaction, and low repeat purchase intention towards Kopi Kenangan products. The study focuses on enhancing brand trust, improving perceived product quality, and increasing customer satisfaction to build customer loyalty towards Kopi Kenangan. Data were collected from 96 customer samples through a questionnaire using probability sampling and analyzed using a structural equation model. The research findings indicate that brand trust has a significant negative influence on customer satisfaction and brand loyalty, while perceived quality has a significant positive influence on customer satisfaction and brand loyalty. Additionally, customer satisfaction also has a significant positive influence on brand loyalty. Furthermore, brand trust and perceived quality together have a positive and significant influence on brand loyalty. Moreover, brand trust has a significant negative influence on brand loyalty through customer satisfaction, while perceived quality has a significant positive influence on brand loyalty through customer satisfaction.